On the Relationship Between Adolescent and Adult Conviction Frequencies - Paternoster, Raymond (Journal of quantitative criminology, 2001)
It is well documented that there is a strong association between involvement in adolescent delinquency and involvement in adult criminality. However, the association is not perfect. Some juveniles who offend at high rates do not go on to offend as adults while some do. Some juveniles who offend at low rates go on to offend as adults while some do not. The reasons for these behavioral changes are not yet well understood. Some criminologists contend that changes in behavior between the adolescent and the adult years are due to processes that occur during the adult years, while others contend that all important adult crime-producing processes operate before the end of an adolescence. In this paper, we use data from the Cambridge Study in Delinquent Development to investigate the empirical merit of the second position. Specifically, after conditioning on adolescent offending behavior, we ask whether variation in adult offending is consistent with a conditional random process. Our analysis suggests an affirmative answer to this question. Although our results do not prove that this “conditionally random” explanation is the process that generates the data, they do suggest that models making this prediction cannot be easily dismissed.